The PAr index, an indicator reflecting altered vitamin B-6 homeostasis, is associated with long-term risk of stroke in the general population: the Hordaland Health Study (HUSK). Issue 1 (26th January 2018) - Zuo, Hui; Tell, Grethe S; Ueland, Per M; Nygård, Ottar; Vollset, Stein E; Midttun, Øivind; Meyer, Klaus; Ulvik, Arve
ABSTRACT: Background: Vitamin B-6 homeostasis is altered during inflammation and immune activation. It is unknown whether altered vitamin B-6 homeostasis is associated with the risk of stroke. Objective: We investigated the relation between the ratio plasma 4-pyridoxic acid: (pyridoxal + pyridoxal-5′-phosphate) (PAr) as an indicator of altered vitamin B-6 homeostasis and the risk of stroke in the general population. Design: We conducted a prospective analysis of the community-based Hordaland Health Study (HUSK) in 6891 adults (born during 1925–1927 and 1950–1951) without known stroke at baseline (1998–1999). Participants were followed via linkage to the CVDNOR (Cardiovascular Disease in Norway) project and the Cause of Death Registry. HRs and 95% CIs were calculated using Cox proportional hazards analyses. Results: A total of 390 participants (193 men and 197 women) developed stroke over a median follow-up period of 11 y. Study participants with elevated PAr experienced a higher risk of incident stroke in an essentially linear dose-response fashion. The HR (95% CI) for the highest compared with the lowest quartile of PAr was 1.97 (1.42, 2.73; P -trend <0.001) for total stroke and 2.09 (1.42, 3.09; P -trend <0.001) for ischemic stroke after adjustment for age, sex, body mass index (BMI), smoking, education, physical activity, estimated glomerular filtration rate, hypertension, diabetes, total cholesterol, and statin use. PAr had greater predictive strength than did C-reactive protein, current smoking, diabetes, hypertension, estimated glomerular filtration rate, and physical activity. The associations were similar in subgroups stratified by age group, sex, BMI, current smoking, hypertension, diabetes, and statin use at baseline. Conclusions: Higher plasma PAr was independently associated with increased risk of incident stroke in all participants and across all subgroups stratified by conventional risk predictors. Our novel findings point to and expand the range of inflammation and immune activation processes that may be relevant for the pathogenesis and prevention of stroke. This trial was registered at clinicaltrials.gov as NCT03013725.